The Essentials of Composite Materials : A Guide for Engineering and Beyond. - Pacheco, Germán A. (CRC Press, 2025)
The Essentials of Composite Materials: A Guide for Engineering and Beyond combines the theory of composite materials and their applications, with a focus on the main industries where they are used. Using the author's experience as a naval architect, boat builder, and composites designer, this book offers a guide to the selection of the most appropriate production processes, procedures, and materials for a particular project. It comprehensively covers polymer matrix composites, explaining what composite materials are, their components, and what they can be used for. Combines theoretical material with practical examples in a uniquely accessible way. Explores fabric structures, materials, resins, procedures, and manufacturing processes, including details that can only be discovered through hands-on work. Covers the more analytical side, explaining classical laminate plate theory, composite systems, strength, and failure criteria. Discusses applications in automotive, aerospace, civil, medical device, and naval industries.This text serves as a practical tool for readers working in the composite fields as well as those looking to enter it.